Stimulation challenge test after STN DBS improves satisfaction in Parkinson's disease patients. (December 2019) - Geraedts, V.J.; van Hilten, J.J.; Marinus, J.; Mosch, A.; Naarding, K.J.; Hoffmann, C.F.E.; van der Gaag, N.A.; Contarino, M.F.
Abstract: Objective: Although subthalamic Deep Brain Stimulation (STN DBS) is proven effective in improving symptoms of Parkinson's Disease (PD), previous literature demonstrates a discrepancy between objective improvement and patients' perception thereof. We aimed to examine whether postoperative stimulation challenge tests (SCT) alters patients' satisfaction after STN DBS for PD. Methods: Fifty-four PD patients underwent preoperative levodopa challenge tests and were routinely invited for SCT 1-2 years postoperatively. SEverity of predominantly Nondopaminergic Symptoms in PD (SENS-PD) scores quantified non-dopaminergic disease severity. Motor functioning was quantified using Movement Disorders Society Unified Parkinson's Disease Rating Scale (MDS-UPDRS) III scores; a ratio between conditions ON and OFF (preoperative Med-ON vs. Med-OFF, and postoperative Med-ON/Stim-ON vs. Med-OFF/Stim-OFF) reflected treatment benefit. 'Global Impression of Change' (GIC) and 'Global Satisfaction with Surgery' (GSS) Likert scales were filled out before and immediately after SCT. Results: Postoperative Med-ON/Stim-ON severity was lower than preoperative ON severity. Disease severity scores were not different between assessments. GIC and GSS scores were higher after SCT versus before (GIC: Z = -3.80, r = 0.37, subjects indicating maximum scores before SCT: 32.1%, after SCT: 57.1%; GSS: Z = -3.69, r = 0.35, maximum scores before SCT: 25.0%, after SCT: 46.4%). Higher non-dopaminergic disease severity was associated with lower GIC and GSS scores (GIC: OR 1.2 (95%CI 1.0–1.3); GSS: OR 1.2 (95%CI 1.1–1.3), while motor-scores and magnitude of DBS-effects were not. Conclusion: SCT improves patients' satisfaction and is recommended especially in case of suboptimal subjective valuations. This information should be considered in clinical practice and in the context of clinical trials. Highlights: Several patients report negative valuations after STN DBS for Parkinson's Disease. Stimulation challenge tests alter patients' perceived impression of DBS effects. Postoperative satisfaction is increased after a stimulation challenge test. Stimulation challenge tests appear recommended in case of suboptimal satisfaction.